1998
DOI: 10.1021/jm9800806
|View full text |Cite
|
Sign up to set email alerts
|

Pyrimidine Thioethers:  A Novel Class of HIV-1 Reverse Transcriptase Inhibitors with Activity Against BHAP-Resistant HIV

Abstract: A series of pyrimidine thioethers was synthesized and evaluated for inhibitory properties against wild-type HIV-1 reverse transcriptase (RT) and an RT carrying the resistance-conferring mutation P236L. Modifications of both the pyrimidine and the functionality attached through the thioether yielded several analogues, which demonstrated activity against both enzyme types, with IC50 values as low as 190 nM against wild-type and 66 nM against P236L RT. Evaluation of a select number of pyrimidine thioethers in cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 24 publications
1
40
0
1
Order By: Relevance
“…Substitution of the sulphur with oxygen or nitrogen decreased or removed the activity. Oxidation of the sul- Nugent et al (1998). phur diminished the activity, and removal of the methylene linker resulted in compounds devoid of activity.…”
Section: Pyrimidine Thioethersmentioning
confidence: 99%
See 1 more Smart Citation
“…Substitution of the sulphur with oxygen or nitrogen decreased or removed the activity. Oxidation of the sul- Nugent et al (1998). phur diminished the activity, and removal of the methylene linker resulted in compounds devoid of activity.…”
Section: Pyrimidine Thioethersmentioning
confidence: 99%
“…phur diminished the activity, and removal of the methylene linker resulted in compounds devoid of activity. Table 16 shows some of the compounds with activity against wildtype and the delavirdine-resistant HIV-1 (P236L) mutant (Nugent et al, 1998). Further study within the pyrimidine thioethers for compounds with broad activity against several NNRTI-resistant variants of HIV-1 have led to the furo[2,3-c]pyridinethiopyrimidine class of compounds.…”
Section: Pyrimidine Thioethersmentioning
confidence: 99%
“…8) Thereafter, many pyrimidine derivatives emerged as anti-HIV agents. 9,10) Against the background of these reports, we undertook a search for an anti-HIV agent by the structure-activity relationship (SAR) of the 1,3-disubstituted uracil 11) . It is demonstrated that the introduction of a cyanomethyl group onto N1 of uracil is effective for anti-HIV-1 activity.…”
mentioning
confidence: 99%
“…They are precursors to important organic compounds [3][4][5] and organometallic complexes [6][7][8]. In addition, they can also be utilized in the determination of many metal ions (Pb, Ru, Bi, Pd, Pt) as selective and sensitive ligands in analytical chemistry [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%